Sex-specific gut microbiome dynamics in Labeo catla: links to reproductive hormones, metabolic dimorphism, and environmental factors - Sundaray, Jitendra Kumar; Mohapatra, Madhusmita; Rasal, Avinash; Udit, Uday Kumar; Mohanty, Sriprakash; Mohanty, Debasrita; Das, Ipsita Iswari; Sahoo, Lakshman; Sahoo, Pramoda Kumar (Frontiers in Microbiology, 2025)
IntroductionGut microbiota play a critical role in aquaculture by enhancing nutrient metabolism, digestion, immune response, and reproductive performance in fish. Labeo catla, one of the most commercially important Indian major carps, demands better reproductive management; however, insights into its gut microbiome composition and functional dynamics, particularly during the crucial pre-spawning phase, remain limited.MethodsIn this study, we investigated the structural and functional attributes of gut microbial communities in male and female L. catla reared in ICAR-CIFA ponds using high-throughput Illumina MiSeq 16S rRNA gene sequencing and examined their associations with reproductive traits.Results and discussionHistological analysis confirmed active gametogenesis in both sexes, while hormonal assays showed higher estradiol levels in females compared to males. Microbiome profiling revealed Proteobacteria as the dominant phylum, followed by Fusobacteria, Bacteroidetes, and Firmicutes. Cetobacterium and Shewanella were the most prevalent genera, with sex-specific differences in microbial diversity and composition. Functional prediction analysis identified genes associated with reproduction, lipid metabolism, digestion, and immunity. Correlation studies revealed a negative association between Bacteroidetes and 11-KT, while Shewanella and Serratia showed positive correlations with estradiol, indicating a potential role of gut microbes in modulating reproductive readiness. Canonical Correspondence and variance partitioning analyses revealed that gut microbiome variation in male and female L. catla was predominantly influenced by biological factors (63.97%) compared to environmental factors (20.99%). Notably, despite their low abundance, Clostridium perfringens and Pseudomonas stutzeri were identified as keystone taxa significantly shaping microbial network structure and stability.ConclusionThis study provides the first comprehensive insight into the sex-specific gut microbiome's dynamics in L. catla during the pre-spawning season and highlight their application in broodstock management and sustainable aquaculture practices.